2022
DOI: 10.25082/amler.2022.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The web-based behavior of online learning: An evaluation of different countries during the COVID-19 pandemic

Abstract: COVID-19, a pandemic that the world has not seen in decades, has caused several new obstacles for student learning and education throughout the globe. As a consequence of the worldwide surge of COVID-19 instances, several schools and institutions in almost every region of the globe have closed in 2020 or switched to online or remote learning, which will have a variety of repercussions for student learning. This has led to educators and students spending more time online than ever before, with both groups resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…Although the importance of learning and teaching in the content of IM has drawn significant scientific attention over the last years, very few studies were found to focus on interventional studies and their effectiveness (Aguayo et al, 2022;Mohammed, 2022). Specifically, studies that use quantitative data or assess the impact of an educative education on students learning and IM competencies are scarce, and teachers are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of learning and teaching in the content of IM has drawn significant scientific attention over the last years, very few studies were found to focus on interventional studies and their effectiveness (Aguayo et al, 2022;Mohammed, 2022). Specifically, studies that use quantitative data or assess the impact of an educative education on students learning and IM competencies are scarce, and teachers are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide pandemic has had many impacts on learning-teaching activities. More than %94 students worldwide have been affected by pandemics, and this situation indicates the extent of the pandemic impact on education across the globe (Mohammed, 2022). During this process, stakeholders of education, teachers, students, institutions, and parents have been involved in a new education process and have entered the distance education course apart from the face-to-face education activities they are used to and had many problems (Poultsakis et al, 2021).…”
Section: Problems Experiencedmentioning
confidence: 99%
“…In this way, the trainer creates a support framework that contributes significantly to self-regulated learning. Therefore, in distance education, there is a transition from the traditional teacher-centered learning model to the student-centered model (Sarakatsanou & Vassala, 2011;Mohammed, 2022).…”
Section: Active Teachingmentioning
confidence: 99%